Implementasi Pembelajaran Berdiferensiasi pada Materi Norma dan Adat Istiadat untuk Meningkatkan Hasil Belajar Peserta Didik - Sukma Laila Nur Jannah; Hery Setiyawan; Rizky Widyaningrum (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Differentiated learning is an effort to provide facilities to students, apart from that providing these facilities provides a lot of new understanding for teachers to see students' needs. This research uses the PTK research method (classroom action research) which is carried out in grade 4 elementary schools with the aim of improving learning outcomes on norms and customs material for students. The results of this research are that it can improve student learning outcomes with the KKN targets set by the school in the material on norms and customs in grade 4 elementary school. Apart from that, the application of differentiated learning is the first application in this class using 3 different results according to the students' abilities.